What’s holding girls back? : Exploring the role of field beliefs in accounting for the gender gap in undergraduate academic fields in Singapore - Chua, Athena Pei Fen (Nanyang Technological University, 2021)
Female underrepresentation in certain academic fields (e.g., Science, Technology, Engineering and Mathematics fields; STEM fields) continues to be a pervasive phenomenon cross-culturally. Studies have found evidence that field-specific ability beliefs (brilliance), which are beliefs regarding a field’s emphasis on brilliance to succeed, can account for this underrepresentation and this relationship suggests the underlying presence of the gender-brilliance stereotype. However, this study proposes that field-specific ability beliefs (science), which are beliefs regarding a field’s emphasis on math and science, can also account for female underrepresentation, and this relationship may suggest the presence of another major gender stereotype, the gender-science stereotype. Hence, this study aimed to examine the predictive validity of field-specific ability beliefs (brilliance) and field-specific ability beliefs (science) in accounting for female underrepresentation in undergraduate academic fields in an Asian country such as Singapore. We surveyed 1498 Nanyang Technological University (NTU) undergraduates across the 35 STEM and non-STEM undergraduate programs offered in NTU. Results indicated that field-specific ability beliefs (science), indicated by the STEM indicator and the systemizing-empathizing cognitive style, were correlated to female representation. Using hierarchical linear regressions, we found that the systemizing-empathizing cognitive style explained for female representation across fields, above and beyond what could be accounted for by field-specific ability beliefs (brilliance) and the STEM indicator. This suggests that in the context of Singaporean undergraduates, field-specific ability beliefs (science), and in particular the perceived cognitive style emphasized on in a field, may be more predictive of female representation as compared to field-specific ability beliefs (brilliance).